(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The article deals with the role and features of the application of conceptual metaphor in the psychotherapeutic discourse (PD). I. Yaloms stories "The Schopenhauer Cure" and "Mommy and the Meaning of Life" are the source of data. Introduction: The purpose of this article is to analyze the metaphorical language of PD integrated into I. Yaloms fiction. Metaphor is a safe way to verbalize forbidden topics with a client during the psychotherapeutic sets, to create a safe space, to achieve a good setting, to reduce the clients resistance, to shift the conversation from unconsciousness to consciousness, etc. Conceptual metaphor is a tool to understanding the deepest layers of the communication between the client and his analyst. Russian linguist Vladimir Karasik refers PD to the medical discourse (MD); but the presence of conceptual metaphors as well as other features makes it possible to distinguish this discourse into an independent one. The relevance of linguistic analysis lies in the need to expand discourses of helping professions (DHP), as well as in the fact that at the present level of the functioning of MD requires using PD. Methodology and sources: The article is based on the main provisions of the theory of conceptual metaphor (CM), proposed by J. Lakoff and M. Johnson. The methodological basis of the analysis carried out in the article are works discussed the PD and the metaphorical language of psychotherapy (I. V. Karasik, A. R. Markin, M. S. Grineva, E. V. Ermolaeva, etc.). The artistic texts by the American practitioner, psychotherapist, and the author of psychological tales Irwin Yalom are the date of the analysis of the PD included in fiction (PDIF). Results and discussion: The article deals with the PD as an independent one, describes the types of CM implied in PD that based on texts analysis. Among the main conceptual metaphors in the PD of this paper there are some CM, such as "dispute is a war", dispute is a dance, "time is money", life is a cruise, orientation metaphors, where the UP-position is associated with the concept of mental health, well-being, altruism, strength, high status, rationality, and the DOWN-position with images of illness, failure, low social status and emotionality. The paper illustrates how the metaphors can help to understand a problem deeper, to improve the contact between the therapist and the client(s), and to facilitate the clients transition from the conceptual "bottom" to the conceptual "top" in the therapeutic process. Along with the conceptual metaphors, there are some author’s classical metaphors in the texts, which help to make artistic texts more fascinating for readers.